A critical-discourse study of the representation of unaccompanied foreign minors in a sample of the Spanish press - Martínez Lirola, María (2023)
The arrival of unaccompanied foreign minors (UFM) to Spain has increased in the last decades. The objective of this article is to study the discursive representation of UFM in a sample of the Spanish press to deepen the understanding of how they are portrayed The data consist of a corpus of all the news items on UFM published in the digital editions of the newspapers El País, ABC and El Mundo from January 1st 2012 to January 1st 2022. The methodology is mixed, i.e. quantitative data will be obtained using the software Antconc for concordance analysis and cluster lists. Thus, a corpus-linguistic analysis is made to observe the main linguistic patterns associated with UFM. Moreover, qualitative data will be offered by using the discursive model of social actors proposed by Van Leeuwen (2008). This model will be used to delve into the main categories employed by the Spanish press to refer to UFM, for this purpose, patterns of assimilation vs individualization and role allocation and identification are described. The study reveals that UFM are mainly associated with criminalization and exclusion. Thus, their representation is associated with social problems.